Analysis of Child Custody Following Divorce Caused by Apostasy Under Positive Law and Islamic Legal Frameworks (Case Study: Case No. 1189/Pdt.G/2023/PA.Tnk) - Antonio, Brian; Wardhani, Sri Pramudya (Yayasan Kawanad, 2025)
This study examines the Tangerang Religious Court's ruling in case number 1189/Pdt.G/2023/PA.Tnk, focusing on child custody disputes arising from apostasy within marital dissolution. The research investigates how Islamic civil law operates within Indonesia's judicial framework, particularly when religious conversion becomes a determining factor in custody arrangements. Employing a normative juridical approach alongside descriptive analytical methods, the investigation draws primary data from court rulings, trial documentation, and judicial reasoning articulated by the panel of judges. Secondary sources encompass statutory regulations, Islamic jurisprudence literature, scholarly journals, and pertinent reference materials. The theoretical foundation rests on Classical Islamic Law principles articulated by Imam Syafi'i, which address the legal implications of apostasy on marital bonds and parental rights, complemented by legal interpretation frameworks developed by Dr. Yahya Harahap, SH., MH., regarding procedural justice in religious courts. The research reveals tensions between protecting children's religious upbringing and applying established custody principles that typically favor maternal care for young children. Findings demonstrate how judges navigate between statutory law, Islamic jurisprudence, and the best interests of the child when apostasy disrupts conventional custody determinations.